A surprising way to control the charge transport in molecular electronics: the subtle impact of the coverage of self-assembled monolayers of floppy molecules adsorbed on metallic electrodes - Bâldea, Ioan (Complex molecular surfaces and interfaces, 2017)
Inspired by earlier attempts in organic electronics aiming at controlling charge injection from metals into organic materials by manipulating the Schottky energy barrier using self-assembled monolayers (SAMs), recent experimental and theoretical work in molecular electronics showed that metal-organic interfaces can be controlled via changes in the metal work function that are induced by SAMs. In this paper we indicate a different route to achieve interface-driven control over the charge transfer/transport at the molecular scale. It is based on the fact that, in floppy molecule based SAMs, the molecular conformation can be tuned by varying the coverage of the adsorbate. We demonstrate this effect with the aid of benchmark molecules that are often used to fabricate nanojunctions and consist of two rings that can easily rotate relative to each other. We show that, by varying the coverage of the SAM, the twisting angle φ of the considered molecular species can be modified by a factor of two. Given the fact that the low bias conductance G scales as cos2 φ, this results in a change in G of over one order of magnitude for the considered molecular species. Tuning the twisting angle by controlling the SAM coverage may be significant, e.g., for current efforts to fabricate molecular switches. Conversely, the lack of control over the local SAM coverage may be problematic for the reproducibility and interpretation of the STM (scanning tunneling microscope) measurements on repeatedly forming single molecule break junctions.